2020
DOI: 10.1016/j.est.2020.101749
|View full text |Cite
|
Sign up to set email alerts
|

Single-tank thermal energy storage systems for concentrated solar power: Flow distribution optimization for thermocline evolution management

Abstract: Concentrated Solar Power (CSP) technology captures solar radiation and converts it into heat for electricity production. It has received an increasing attention because integrated thermal energy storage (TES) systems can largely enhancing the reliability and the dispatchability. Over the last decade, low-cost single storage tank based on the thermocline technology becomes an alternative to commonly-used two-tank TES system. However, the improper inlet/outlet manifolds may cause the strong mixing of hot and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Under these circumstances, the intentional flow non-uniform distribution may be a better option to be adapted to decrease the local maximum temperature, as pointed out by Kumar and Singh [13]. This is actually in line with some observations reported in the literature [30][31][32] in that the optimal flow distribution is usually not uniform but obeys certain trends subjected to a defined optimization objective and constraints. In this regard, Kumar and Singh [13] indicated that the flow arrangement and the actual flow distribution should fit the heat flux shape to achieve a better thermal performance, i.e., lower maximum temperature and thermal resistance.…”
Section: Introductionsupporting
confidence: 79%
“…Under these circumstances, the intentional flow non-uniform distribution may be a better option to be adapted to decrease the local maximum temperature, as pointed out by Kumar and Singh [13]. This is actually in line with some observations reported in the literature [30][31][32] in that the optimal flow distribution is usually not uniform but obeys certain trends subjected to a defined optimization objective and constraints. In this regard, Kumar and Singh [13] indicated that the flow arrangement and the actual flow distribution should fit the heat flux shape to achieve a better thermal performance, i.e., lower maximum temperature and thermal resistance.…”
Section: Introductionsupporting
confidence: 79%
“…The capacity ratio (σ) is the ratio of the actual stored thermal energy to the maximum energy storage capacity [12],…”
Section: Category #1mentioning
confidence: 99%
“…In practice, a high-steep slope for the outlet temperature curve is expected to have a positive effect on the capacity ratio. Thus, as a data analysis, a dimensionless indicator called the tail factor is calculated from the dimensionless outlet temperature profile against the dimensionless time [12]. The tail factor is independent on the thermal properties of HTF, the geometries, and the operating conditions.…”
Section: Category #1mentioning
confidence: 99%
See 2 more Smart Citations